Efektifitas Larutan Daun Gelinggang (Cassia alata L.) dalam Menghambat Kejadian Penyakit Antraknosa (Colletotrichum sp.) pada Tanaman Cabai Rawit - Janah, Norhuda Ariatul; Fitriyanti, Dewi; Aidawati, Noor (JURNAL PROTEKSI TANAMAN TROPIKA, 2025)
This research uses vegetable pesticides from gelinggang leaf solution which aims to determine the effectiveness of gelinggang leaf solution in inhibiting the incidence of the fungus Colletotrichum sp. on cayenne pepper plants. The research used a completely randomized design (CRD) with one factor consisting of 6 treatments with 4 replications, each treatment unit consisting of 2 plants so that the total number of plants tested was 48 experimental units. The treatments used were without treatment (T0), chemical treatment (TM) 5% gelinggang leaf solution (T1), 10% gelinggang leaf solution (T2), 15% gelinggang leaf solution (T3) and 20% gelinggang leaf solution (T4) . The research results showed that the gelinggang leaf solution was effective in inhibiting the incidence of anthracnose. With the lowest percentage of disease incidence at 31.3%, treatment was T4, followed by treatment T3 at 32.5%, T2 at 36.3%, different from no treatment (control), which was 47.5.